2020
DOI: 10.1002/adom.202000143
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow Optical and Electrical Losses via Metal‐Assisted Chemical Etching of Antireflective Nanograss in Conductive Mesh Electrodes

Abstract: Various types of anti‐reflective technologies are capable of increasing the light absorption of optical devices. The electrical conductivity of the collected carriers must also be increased for efficient photoelectric conversion. However, increasing the front electrode area reduces the amount of light absorption, causing shading and resistive losses to conflict in front‐illuminated devices. In this study, a low‐reflectance surface and high‐conductance electrode for Schottky photodiodes are fabricated using met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Nevertheless, the comparison indicates that there is still room for improvement in the performance of MACE photodiodes. Indeed, as reported in the literature [27], even lower reflectance should be achievable by MACE. Likewise, as seen earlier in Fig.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, the comparison indicates that there is still room for improvement in the performance of MACE photodiodes. Indeed, as reported in the literature [27], even lower reflectance should be achievable by MACE. Likewise, as seen earlier in Fig.…”
Section: Resultssupporting
confidence: 61%
“…While MACE has previously been applied to Schottky photodiodes [26], [27], it is well known that they always suffer from high dark current and, consequently, have limited sensitivity. For instance, Zhang et al [26] have recently reported a high-responsivity MACE Si Schottky photodiode; however, the achieved dark current density is as high as 130 nA cm −2 at −1-V bias, which cannot compete with commercial Si photodiodes (typically <10 nA cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the etched surface and metal catalyst maintain contact throughout the etching process. MACE has been used in various fields such as electronics, 17,18 optoelectronics, [19][20][21] and energy harvesting. [22][23][24] Although MACE has some advantages over dry etching, the current technique cannot be utilized in the complementary metal oxide semiconductor (CMOS) process because of the use of noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…The method can be readily extended to fabricate novel wide bandgap semiconductor structures and devices. [32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 99%